Respuesta :

Answer:

x = - 2 2/3

y =  - 4 1/3

Step-by-step explanation:

-4x -2y = - 2

4x +8y = -24

Now if you just add those 2 equations, what will happen is that the xs will cancel. They are equal but opposite in sign

6y = - 26              Now divide by 6

6y/6 = -26/6        Combine

y = - 4 2/6 = - 4 2/6

y = - 4 1/3

Now use the top equation to find x

-4x - 2(-4 1/3) = - 2

-4x +  8 2/3 = - 2                     Subtract 8 2/3 from both sides

- 4x = - 2 - 8 2/3                     Combine

- 4x = - 10 2/3                         Divide by - 4

x = - 10 2/3 / - 4

x = - 2 2/3          

9514 1404 393

Answer:

  (x, y) = (8/3, -13/3)

Step-by-step explanation:

The x-coefficients are opposites, so the x-terms can be eliminated simply by adding the equations.

  (-4x -2y) +(4x +8y) = (-2) +(-24)

  6y = -26

  y = -26/6 = -13/3

Substituting into the first equation gives ...

  -4x -2(-13/3) = -2

  2x -13/3 = 1 . . . . . . . . divide by -2

  2x = 16/3 . . . . . . . . . add 13/3

  x = 8/3

The solution is (x, y) = (8/3, -13/3).